Epistemological foundations of physical, sports, and artistic activities and the corporeality of practitioners. What are the effects of didactic transposition in physical education? - Lenzen, Benoît; Cordoba, Adrián (Swiss Journal of Educational Research, 2018)
The history and epistemological foundations of physical, sports, and artistic activities (APSA) may enable us to infer the specialized corporeal elements they carry. The didactic processing of APSA carried out by physical education teachers may contradict student’s daily corporeal transformation or may create indifference to these corporeal elements specific to APSA. To support and illustrate this thesis, we describe two learning situations (respectively in basketball and handball) constructed and presented by students in physical education during supervised placements.